Research progress on the kidney-gut-brain axis in brain dysfunction in maintenance hemodialysis patients - Yu, Jie; Li, Yulu; Zhu, Bin; Shen, Jianqin; Miao, Liying (Frontiers in Medicine, 2025)
Maintenance hemodialysis (MHD) has become the primary renal replacement therapy for patients with end-stage renal disease. The kidney-gut-brain axis represents a communication network connecting the kidney, intestine and brain. In MHD patients, factors such as uremic toxins, hemodynamic changes, vascular damage, inflammation, oxidative stress, and intestinal dysbiosis in MHD patients refers to a range of clinical syndromes, including brain injury, and is manifested by conditions such as white matter disease, brain atrophy, cerebrovascular disease, cognitive impairment, depression, anxiety, and other behavioral or consciousness abnormalities. Numerous studies have demonstrated the prevalence of these brain disorders in MHD patients. Understanding the mechanisms of brain disorders in MHD patients, particularly through the lens of kidney-gut-brain axis dysfunction, offers valuable insights for future research and the development of targeted therapies. This article reviews the brain dysfunction associated with MHD, the impact of the kidney-brain axis, intestinal barrier damage, gut microbiota dysbiosis caused by MHD, and the role of the gut-brain axis in brain dysfunction.